A methods engineering study on Jelyn Garments Corporation - Dagondon, Elmer; Manuel, Jelle Jasmin M.; Pajo, Novelyn L. (Diliman, Quezon City College of Engineering, 2001)
Jelyn Garment Corporation, based on in Marilao, Bulacan, manufactures infants and children's knitwear such as cardigans, sweaters, pullovers, cover-allls, blankets, shawls, and booties. The group chose the cardigans type of knitwear as the primary focus of the study based on the demand for the product. Through the use of Streamline Diagnosis Chart and Cause and Effect Diagrams, the following problems were identified : excessive movement of materials and underutilized workers. At most three alternatives were generated for each aforementioned problem. For delay in production, it is recommended that a schedule of supervision be followed. To solve excessive movement of materials, the group suggested that the machine layout be rearranged, and materials should have closed mobile cabinets as permanent storage and plastic temporary storage bins in the role of transportation equipment inside the plant. In order to utilize workers fully, the group proposed a working scheduel which when adhered to be the workers would reduce their idle time significantly. An accelerated piecework incentive plan and a set of workers' attire is suggested as well, for the purpose of motivating workers and increasing their morale. It is suggested that in the first week of implementation, the management should introduce the workers to the changes in the system and rationalize why the transformations are to be carried out. Secondly, two week trial periods are alloted so that the workers would be settled on to adjust to the fresh organization. By the third week, supervisors are tasked to appraise the consequences and outcome of the modifications. After which, the management shall deliberate on whether the new course of action should be incessantly adhere to or accustomed to the feedback of the workers. The possible conflict that may happen when the recommendations are implemented are : complaining supervisors because of additional workload, displeased workers, fluctuating amount of output, and minimum reduction in workers' idle time. These problems are triggered by low morale and complain from workers, high inconsistency, in the quality and amount of output and not meeting the quota. To prevent these critical troubles, the board must be able to allot allowances to the workers, look into fields of discontent, anticipate demands of the product and evaluate the existing system.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Clothing trade; Systems analysis